DESKRIPSI PERANCANGAN PERANGKAT LUNAK APLIKASI KULIMAS DALAM PENGEMBANGAN KULINER BANYUMAS - Diyan Febriana Nur Utami; Anisa Lidia Fitri; Feni Resti Anti; Citra Wiguna (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Culinary is an activity related to cooking or cooking activities. Culinary can also be interpreted as processed products in the form of side dishes, snacks and drinks. Culinary is inseparable from cooking activities which are closely related to daily food consumption. Culinary development in Banyumas is currently growing rapidly. Also The number of restaurants/restaurants in Banyumas is growing rapidly, this indicates that the culinary world in Banyumas has a large market opportunity in the culinary field. KULIMAS (Kuliner Banyumas) is a website-based application as a culinary information service in Banyumas. The features available in the KULIMAS application are: online place reservations without the need to come to a restaurant or cafe directly, can manage information data, update prices, display updates, can place orders, schedule reservations, select locations, select menus and pay . The design of the KULIMAS application is in the form of a Dokumen Deskripsi Perancangan Perangkat Lunak (DPPL) which is an analysis and design that is made in detail in the design document. Keywords: Culinary, Banyumas Culinary, Application Development